OBSTETRICAL ASSOCIATED RENAL, CORTICAL NECROSIS: THOUGH UNCOMMON BUT NOT RARE! - Ali, Akhtar; Ali, Mahrukh Ayesha; Ali, Mohammad Usman (Journal of Ayub Medical College Abbottabad, 2010)
Background: Renal cortical necrosis (RCN) carries high morbidity and mortality in South East Asia. The purpose of this study was to look specifically at the incidence of obstetrical related RCN in renal biopsies and to evaluate its precipitating factors. In addition, prognosis, impact of aetiology and outcomes on discharge were also considered. Methods: The study was conducted in the Department of Nephrology, Lady Reading Hospital Peshawar, Pakistan. Renal biopsies of 1,670 patients were analysed during the study period of 1998 to 2008. All the patients with obstetrical related RCN were included. Patient records, demographic data, urine output on admission and preceding history of antepartum haemorrhage (APH), post-partum haemorrhage (PPH), septicaemia, operative interventions and retained product of conception (ROPC) was noted and need for dialysis was considered. Results: Out of 1670 kidney biopsies analysed, 48 turned out to be RCN. Among them 39 patients (81.3%) had diffuse cortical necrosis, 6 patients (12.5%) had patchy cortical necrosis with ATN while 3 patients (6.3%) had predominant ATN with partial patchy cortical necrosis. Out of 48 patients, 25 (52.1%) were oliguric, 18 (37.5%) were anuric while 5 (10.4%) had urine output >800 ml 24 hr. Operative interventions were found in 29 patients while 19 patients had normal vaginal delivery (NVD). 16 (55.2%) patients with operative intervention had PPH. Thus the association proved to be significant (p= 0.037). Conclusion: Overall incidence of RCN was 2.9%. Oliguria/anuria on admission and dialysis dependency are associated with RCN. PPH and history of operative intervention have significant association and are contributing factors to development of RCN. Keywords: Renal cortical necrosis (RCN), post-partum haemorrhage (PPH), ante-partum haemorrhage (APH), acute renal failure (ARF), dialysis